(untitled) (ENTHYMEMA, 2019)
The psychoanalytical talking cure is interested beyond the speech act or linguistic act in language as a “structure” in the multiple sense: as a bearer of knowledge concerning pleasure/jouissance in the form of cultural imperatives (ideal demands, prohibitions and commands) in myths, fairy tales, jokes, and other manifestations of high and popular culture, and as a grammar i.e. definition of relations of subject, predicate, object (see Freud on Schreber) as well as an arsenal of logical operations that determine the course of an instinct’s vicissitude: reversal into its opposite, active-passive, turning round upon the subject’s own self, condensation and displacement, etc.text. These structures result from the culture process (as its interim results), emerge from processes of repression and sublimation, which for their part form the current psychic instruments, including those of sublimation and psychoanalytic work. For their part, they form the current psychic instruments, including those of sublimation and psychoanalytic work.